2003
DOI: 10.3758/bf03195811
|View full text |Cite
|
Sign up to set email alerts
|

Who when where: An experimental test of the event-indexing model

Abstract: We tested the event-indexing model proposed by Zwaan, Langston, and Graesser (1995). Participants read narratives containing target sentences that involved situational shifts. Independently of each other, continuity and shifting of the protagonist, time, and location dimensions were varied. In Experiment 1, reading times of the target sentences increased for protagonist shifts and temporal shifts, whereas the effect of spatial shifts was weak. Moreover, an interaction of protagonist shifts and spatial shifts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
74
2
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 16 publications
11
74
2
9
Order By: Relevance
“…Reading time increased consistently at changes in time and cause; reading time sometimes increased at spatial changes, but this depended on the previous knowledge of the reader and task goals. More recent work has found that reading time increases at shifts in characters and their goals [15,16]. Such results support the notion that reading times increase at event boundaries because, as noted previously, event boundaries are associated with changes in time, space, causes, characters and goals.…”
Section: Reading-time Evidence For Automaticity Of Event Segmentationsupporting
confidence: 72%
“…Reading time increased consistently at changes in time and cause; reading time sometimes increased at spatial changes, but this depended on the previous knowledge of the reader and task goals. More recent work has found that reading time increases at shifts in characters and their goals [15,16]. Such results support the notion that reading times increase at event boundaries because, as noted previously, event boundaries are associated with changes in time, space, causes, characters and goals.…”
Section: Reading-time Evidence For Automaticity Of Event Segmentationsupporting
confidence: 72%
“…When a new time frame has been identified, because readers must establish a new temporal framework, a new situation model may be created. Several studies have found increased reading times accompanying temporal shifts (Radvansky & Copeland, 2010;Radvansky et al, 2001;Rinck & Weber, 2003;Zwaan, Magliano, et al, 1995;. However, other studies have found decreases in reading times for historical texts (Radvansky et al, 2001) and in a novel (McNerney et al, 2011).…”
Section: Abstract Situation Models Memory Readingmentioning
confidence: 89%
“…Changes along these dimensions can be thought of as event shifts. A common finding in the literature is that reading times often increase when an event shift is encountered (e.g., Radvansky & Copeland, 2010;Rinck & Weber, 2003;Zwaan, Magliano, & Graesser, 1995;Zwaan, Radvansky, Hilliard, & Curiel, 1998). The aim of this paper is to explore the role of causal unexpectedness as a contributor to the processing of these event shifts.…”
Section: Abstract Situation Models Memory Readingmentioning
confidence: 99%
“…Bien plus, dans la majorité des expériences, les ruptures spatiales n'ont tout simplement pas d'effet sur la vitesse de lecture. Ce résultat a été reproduit récemment par Therriault, Rinck et Zwaan (2006) dans une étude qui combinait la méthode qui vient d'être décrite à une situation expérimentale plus contrôlée (voir aussi Rinck, Weber, 2003). Même s'il faut noter que ces Représentation de l'espace et du temps dans le modèle situationnel construit ...…”
Section: Comparaison Des Deux Conceptionsunclassified